Protease-activated indocyanine green nanoprobes for intraoperative NIR fluorescence imaging of primary tumors. Issue 19 (7th July 2022) - Lew, Benjamin; George, Mebin; Blair, Steven; Zhu, Zhongmin; Liang, Zuodong; Ludwig, Jamie; Kim, Celeste Y.; Kim, Kyekyoon (Kevin); Gruev, Viktor; Choi, Hyungsoo
Abstract : Protease-activated cationic gelatin nanoprobes encapsulating ICG for NIR fluorescence imaging of primary breast tumor with high selectivity and sensitivity. Abstract : Tumor-targeted fluorescent probes in the near-infrared spectrum can provide invaluable information about the location and extent of primary and metastatic tumors during intraoperative procedures to ensure no residual tumors are left in the patient's body. Even though the first fluorescence-guided surgery was performed more than 50 years ago, it is still not accepted as a standard of care in part due to the lack of efficient and non-toxic targeted probes approved by regulatory agencies around the world. Herein, we report protease-activated cationic gelatin nanoparticles encapsulating indocyanine green (ICG) for the detection of primary breast tumors in murine models with high tumor-to-background ratios. Upon intravenous administration, these nanoprobes remain optically silent due to the energy resonance transfer among the bound ICG molecules. As the nanoprobes extravasate and are exposed to the acidic tumor microenvironment, their positive surface charges increase, facilitating cellular uptake. The internalized nanoprobes are activated upon proteolytic degradation of gelatin to allow high contrast between the tumor and normal tissue. Since both gelatin and ICG are FDA-approved for intravenous administration, this activatable nanoprobe can lead to quick clinical adoption and improve the treatment of patients undergoing image-guided cancer surgery.